Surfaces, Interfaces, and Nanostructures: Spectroscopic Characterization and Applications (Phys. Status Solidi B 2/2019). Issue 2 (15th February 2019) - Salvan, Georgeta; Dzhagan, Volodymyr; Vogt, Patrick; Seyller, Thomas
Abstract : The interaction between electromagnetic waves and matter has always been fascinating. Over long time, optical spectroscopies have established themselves as powerful probes of the atomic and electronic structure of crystals and molecules. In combination with a complementary set of electron spectroscopies, they build a universal characterization toolbox for the investigation of surfaces, interfaces, and nanostructures, some of them being interesting for the fundamental understanding of material properties and/or device fabrication – as illustrated by the tetrahedron in the logo of Semiconductor Physics group in Chemnitz (front cover, center). Raman spectroscopy, for instance, being basically a macroscopic technique, can selectively probe down to single monolayers, based on resonance between the exciting light and electronic transitions in the layer. In its surface‐ or tipenhanced configuration, it gains in sensitivity and spatial resolution down to single molecule level. The energy band alignments and the chemical composition information delivered by photoemission spectroscopies are indispensable for construction of devices. On the other hand, spectroscopic ellipsometry provides information on the electronic properties as well as thickness of layered structures. This special issue is a collection of research work representing the up‐to‐date possibilities of spectroscopic characterization of surfaces, interfaces, nanostructures, and thereon based functional structures. It is dedicated to Dietrich R.T. Zahn on the occasion of his 60th birthday (see the Dedication, article no. 1900027 ).